PLURALIST-MULTICULTURAL ISLAMIC EDUCATION AN ATTEMPT TO REDUCE RADICALISM AND ANARCHY TO A PEACEFUL PLURAL SOCIETY - Nudin, Burhan (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2018)
The paper discusses the role of Islamic education in eradicating radicalism and anarchy. It argues that there are many radicalism and anarchy acts that appear in Indonesia and that military/security approach may not be effective in eradicating radicalism and anarchy in Islam. Another approach is required to solve the problem, namely pluralist-multicultural Islamic education. The main purpose of this approach is on understanding and appreciation among students to their own and others’ culture—including religion—and based on Bhinneka Tunggal Ika (Unity in Diversity) as well as Pancasila (the Five Pillars). By applying pluralist-multicultural Islamic education, it is expected that it will be an effective instrument to develop tolerance and peace among students since their early ages; therefore, they will become a pluralist-multicultural generation. In the long run, various radicalism and anarchy acts in Indonesia can be reduced.